Penerapan model discovery learning dengan media manipulatif untuk meningkatkan keterampilan pemecahan masalah volume bangun ruang (kubus dan balok) pada peserta didik kelas V SD - Dewi Zakiyatus Sholihah; Riyadi Riyadi; Sadiman Sadiman (Universitas Sebelas Maret, 2019)
The goal of this research is to increase the space building problem solving skill (beam and cube) on the 5th grade student of SDN Tegalrejo No.98 Surakarta by implementing the discovery learning model with the manipulative media. The form of this research is clasroom action research which is conducted in two cycles. Each of the cycle consist of three meeting. The subject of this research is the twenty two of 5th grade students and teacher of class V at SDN Tegalrejo No.98 Surakarta on the academic year of 2018/2019. The collecting data technique used is observation, interview, test, and documentation. The data validity used is triangualation source, and triangulation technique. The obtained data in the classroom action research is analysed by using descriptive statistical analysis technique and interactive analyses Miles and Huberman Model. The result of the research showed that there is increasment of classical completeness start from 0% on the preaction, become 5% on the cycle 1, and 82% on the cycle II.The conclusion of this research is The Implementation of Discovery Learning Model with manipulative media can increase the space building problem solving skill (beam and Cube) on the 5th gradestudent of SDN Tegalrejo No.98 Surakarta on the acadamic year 2018/2019.